Keragaman Jenis Hasil Tangkapan dan Sinkronisasi Waktu Tangkap Jaring Insang Permukaan di Perairan Ohoi Tuburngil Kabupaten Maluku Tenggara - Julianus Notanubun; Yuliana A. Ngamel; Sergius Bukutubun (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
Fishing using gill net has been done widely by fishermen in Southeast Maluku Regency, including in Ohoi Tuburngil waters north east Kei Besar District. Fishing activities using this type of fishing gear are still ongoing as a source of income for local community. The objective of this research were to (1) analyze the composition of the catch with a surface gill net based on the catching time and (2) compare yields and determine the best fishing time in the fishing process with surface gill net. The research methods were experimental fishing, observation and interview. The results showed that the total number of fish species caught with surface gill net during the research was 128 fish consisting of 7 fish species. The value of the diversity index (H') obtained for fishing in the morning was 1,60, at daytime was 1,15, afternoon was 1,30, and at evening was 0,92. According to the criteria for the diversity index, the value of H' less than 1 is categorized as low diversity. The results of the analysis of variance showed that te fishing time has a very significant effect on the catch number at the level of ά = 0.05. Based on the results obtained, it showed that the evening catch was significantly different from that in the morning, the daytime and the afternoon, while catch in the afternoon was significantly different from the day time and different from the morning time.